DETERMINAN LOYALITAS PELANGGAN APLIKASI LIVIN BY MANDIRI DI KOTA SEMARANG - Safina Pribadi Makna; Amron Amron (Jurusan Ilmu Ekonomi Prodi Ekonomi Pembangunan Fakultas Bisnis dan Ekonomika Universitas Surabaya, 2023)
Mobile Banking can generally be interpreted as an m-commerce application that is supported by mobile technology and products that make it easier for customers to process banking services using mobile phones, including being accessible using smartphones, tablets, smart watches and various other advanced technologies. Banking services are provided by the company to support the course of bank-related activities to customers in order to make it easier for customers to make transactions. This is useful to support the smooth storage and distribution of capital, which is directly related to deposits and credit as well as indirectly. Knowing the effect of Brand Image, Product Quality and Price on Customer Loyalty of Livin by Mandiri application is the purpose of this research. A total of 100 respondents were obtained who had been adjusted to the criteria of being over 17 years old and were users of the Livin by Mandiri application, Where in getting the respondent using the purposive sampling method. In this study, several tests were carried out such as the Validity Test, Reability, Classical Assumptions, T-Test and F-Test. The result of this study is that all variables have a positive impact on customer loyalty, this shows that the better the brand image, product quality and the more affordable the price that can be provided by the company, the more customer loyalty will increase.